2020
DOI: 10.26633/rpsp.2020.46
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial profile of Acinetobacter baumannii at a tertiary hospital in Honduras: a cross-sectional analysis

Abstract: Acinetobacter baumannii is considered to be a worldwide threat to public health due to its high antimicrobial resistance rates and the severe infections it can cause. Little is known about this pathogen’s resistance in Central America. This report aims to describe the antimicrobial resistance profile of A. baumannii at a tertiary hospital in Honduras. The cross-sectional analysis was conducted at the tertiary care laboratory hospital in San Pedro Sula in 2015 – 2017. A total of 113 consecutive microbiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
1
4
0
6
Order By: Relevance
“…The resistance to ciprofloxacin in the different studies is higher than 50% which is in line with the data of our study [23][24][25][26][27][28].…”
Section: Resistance Profilesupporting
confidence: 91%
“…The resistance to ciprofloxacin in the different studies is higher than 50% which is in line with the data of our study [23][24][25][26][27][28].…”
Section: Resistance Profilesupporting
confidence: 91%
“…In the countries where lice were collected, reports of A. baumannii infections are almost exclusively healthcare-associated. For example, in Honduras, a cross-sectional study conducted at a tertiary health care centre reported that the majority of isolates were from patients in the intensive care unit (ICU), with a significant proportion (44%) hospitalized in the pediatric wards (neonatal ICU and general pediatrics) [ 36 ]. In Argentina, carbapenem resistance in A. baumannii has been monitored since the year 2000, and Argentina is the Latin American country with the most scientific reports on this infection [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that both of these bacteria are among ESKAPE organisms (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter) (Zuniga-Moya et al 2020) and significant nosocomial pathogens (Zavascki et al 2010). Furthermore, the problem of drug resistance in P. aeruginosa and A. baumannii limits their treatment of infections.…”
Section: Introductionmentioning
confidence: 99%